Problèmes du travail féminin (Relations industrielles / Industrial Relations, 1952)
The article reviews the book, "Problèmes du travail féminin," by Roger Chartier, proposed for the teaching of labour relations, Centre de culture populaire de Laval, Université Laval, 1952 (61 pages).